A morphological analysis of the Indonesian suffixation: a look at the different types of affixes and their semantic changes - Danang Satria Nugraha, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study delved into the nature of suffixation in Indonesian morphology, analyzing its crucial role in word formation and semantic variations. The presentstudy investigated suffixation patterns, functions, and productivity by scrutinizing a corpus of Indonesian words, i.e., the Indonesian – Leipzig Corpora Collection (ILCC). This exploration used morphosemantics frameworks, two sets of instruments that consisted of verbal construction and noun construction tester, and empirical data to describe suffixation in Indonesian. The results showed that among the various suffixes that shaped the language’s grammatical structure, /-kan/ (50.70% with S-occurrence: 217,208), /-nya/ (19.53% with S-occurrence: 83,648), /-an/ (16% with S-occurrence: 68,524), and /-lah/ (7.76% with S-occurrence: 33,220) emerged as the most prominent ones. Statistically, the mean value of verb suffixation (5.9) was higher than that of noun suffixation (5.6). Among these, /-kan/ primarily signified causation or transformation of a verb into a transitive verb, while /-nya/ indicated possession, /-an/ transformed verbs into nouns, and /-lah/ added an imperative meaning to the word. In terms of semantic modification and nuances, it has been discovered that suffixes like /- kan/, /-i/, and /-an/ change words’ semantic structure in complex ways. The suffix /-kan/, which has a causal or transformational function, modifies the meaning of words by signifying the start of an action. Although /-an/ makes it easier for verbs to become nouns, /-i/ aids in objectification or verbalization. The findings of this study offer implications for the field of Indonesian language description, particularly in the areas of suffixal identification and classification, as well as morphological productivity.